Experimental bacteriophage treatment of honeybees (Apis mellifera) infected with Paenibacillus larvae, the causative agent of American Foulbrood Disease. Issue 1 (2nd January 2016) - Yost, Diane G.; Tsourkas, Philippos; Amy, Penny S.
ABSTRACT: American Foulbrood Disease (AFB) is an infection of honeybees caused by the bacterium Paenibacillus larvae . One potential remedy involves using biocontrol, such as bacteriophages (phages) to lyse P. larvae . Therefore, bacteriophages specific for P. larvae were isolated to determine their efficacy in lysing P. larvae cells. Samples from soil, beehive materials, cosmetics, and lysogenized P. larvae strains were screened; of 157 total samples, 28 were positive for at least one P. larvae bacteriophage, with a total of 30. Newly isolated bacteriophages were tested for the ability to lyse each of 11 P. larvae strains. Electron microscopy demonstrated that the phage isolates were from the family Siphoviridae . Seven phages with the broadest host ranges were combined into a cocktail for use in experimental treatments of infected bee larvae; both prophylactic and post-infection treatments were conducted. Results indicated that although both pre- and post-treatments were effective, prophylactic administration of the phages increased the survival of larvae more than post-treatment experiments. These preliminary experiments demonstrate the likelihood that phage therapy could be an effective method to control AFB.